2004
DOI: 10.3732/ajb.91.10.1557
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and diversification of bryophytes

Jonathan Shaw,
Karen Renzaglia

Abstract: The bryophytes comprise three phyla of embryophytes that are well established to occupy the first nodes among extant lineages in the land-plant tree of life. The three bryophyte groups (hornworts, liverworts, mosses) may not form a monophyletic clade, but they share life history features including dominant free-living gametophytes and matrotrophic monosporangiate sporophytes. Because of their unique vegetative and reproductive innovations and their critical position in embryophyte phylogeny, studies of bryophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
116
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(130 citation statements)
references
References 110 publications
1
116
0
4
Order By: Relevance
“…
Phylogenetic analyses of genome structure and nucleotide sequences from mitochondrial, plastid, and nuclear genes have corroborated the view held by botanists for over a century that the bryophyte groups (mosses, liverworts, hornworts) comprise early-diverging land plant lineages that originated before the appearance of vascular plants ( Haeckel, 1876 ;Campbell, 1895 ;Bower, 1935 ;Kenrick and Crane, 1997 ;Shaw and Renzaglia, 2004 ). Early cladistic analyses based on morphological characters ( Mishler and Churchill, 1984 ) showed that the three bryophyte groups, classifi ed by most botanists of the time as a single phylum because of their similar gametophyte-dominant life cycles, more likely represent a paraphyletic grade that diverged before the emergence of the vascular plants.
…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…
Phylogenetic analyses of genome structure and nucleotide sequences from mitochondrial, plastid, and nuclear genes have corroborated the view held by botanists for over a century that the bryophyte groups (mosses, liverworts, hornworts) comprise early-diverging land plant lineages that originated before the appearance of vascular plants ( Haeckel, 1876 ;Campbell, 1895 ;Bower, 1935 ;Kenrick and Crane, 1997 ;Shaw and Renzaglia, 2004 ). Early cladistic analyses based on morphological characters ( Mishler and Churchill, 1984 ) showed that the three bryophyte groups, classifi ed by most botanists of the time as a single phylum because of their similar gametophyte-dominant life cycles, more likely represent a paraphyletic grade that diverged before the emergence of the vascular plants.
…”
mentioning
confidence: 70%
“…In fact, Haeckel ' s (1876) tree similarly shows mosses and liverworts as a paraphyletic grade basal to the vascular plants. Recent data sets appear to favor the hypothesis that liverworts (phylum Marchantiophyta) comprise the earliest-diverging lineage, followed by the mosses (Bryophyta) and hornworts (Anthocerophyta) ( Qiu et al, 1998 ;Nickrent et al, 2000 ;Shaw and Renzaglia, 2004 ). However, the most data-rich studies to date, based on chloroplast or mitochondrial organellar proteins, like analyses based on sperm cell morphology ( Garbary et al, 1993 ), identify a clade uniting liverworts and mosses, and additional data are still needed before we can consider the branching order of early land plant lineages to be fi nally resolved ( Nishiyama et al, 2004 ;Rodr í guez-Ezpeleta et al, 2007 ;Terasawa et al, 2007 ; but see also Qiu, et al, 2006 ).…”
mentioning
confidence: 99%
“…Molecularly based phylogenetic analyses and studies of the cell-wall microstructure of embryophjrtes and related algal clades indicate that charophytes, a green algal clade, are the closest extant relatives of embryophytes [40,42,43] (Box 1). Depending on the study, any of three major bryophyte lineages (liverworts, hornworts or mosses) might be the sister group to vascular plants [40,[44][45][46][47], consistent with the view that bryophytes are a grade rather than a clade [47]. After bryophyte establishment, one to a few extinct groups of protracheophytes diverged [7], one of which gave rise to a monophyletic vascularplant clade defined by robust synapomorphies [45].…”
Section: Continental Ecological Ensembles Of the Mid Paleozoicmentioning
confidence: 86%
“…Marchantiophyta (liverworts), Anthocerotophyta (hornworts), and Bryophyta (mosses) (e.g. Mishler & Churchill 1984, Kenrick & Crane 1997, Shaw & Renzaglia 2004, Qiu et al 2007. Similarly, those plants historically classified as 'pteridophytes' and 'ferns and fern allies'represent a paraphyletic assemblage, including the lycophytes, horsetails, whisk ferns, and all eusporangiate and leptosporangiate ferns (Smith et al 2006).…”
Section: Introductionmentioning
confidence: 99%